2005
DOI: 10.1364/ao.44.005688
|View full text |Cite
|
Sign up to set email alerts
|

Designing a practical system for spectral imaging of skylight

Abstract: In earlier work [J. Opt. Soc. Am. A 21, 13-23 (2004)], we showed that a combination of linear models and optimum Gaussian sensors obtained by an exhaustive search can recover daylight spectra reliably from broadband sensor data. Thus our algorithm and sensors could be used to design an accurate, relatively inexpensive system for spectral imaging of daylight. Here we improve our simulation of the multispectral system by (1) considering the different kinds of noise inherent in electronic devices such as change-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(51 citation statements)
references
References 14 publications
1
49
0
1
Order By: Relevance
“…This has been established in previous works for spectral recovery of reflectances and daylights using simulated sensors when noise effects are not included. 3,12 Nevertheless, a recent study 22 shows that this could not be the case when different kinds of noise are considered; in this case, increasing the number of sensors and͞or the number of eigenvector does not necessarily improve the accuracy of estimated spectra in the multispectral systems.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This has been established in previous works for spectral recovery of reflectances and daylights using simulated sensors when noise effects are not included. 3,12 Nevertheless, a recent study 22 shows that this could not be the case when different kinds of noise are considered; in this case, increasing the number of sensors and͞or the number of eigenvector does not necessarily improve the accuracy of estimated spectra in the multispectral systems.…”
Section: Resultsmentioning
confidence: 99%
“…10,11 Also, the computational design of a multispectral device to estimate the SPD of daylights with a reduced number of both simulated Gaussian and commercial sensors has been proposed. 12,22 In this paper a multispectral device to synthesize SPDs of daylight-type illuminants with high spectral and colorimetric accuracy is proposed. Based on similar techniques developed for spectral image capture of art paintings, 1,6 the algorithm is based on a priori analysis of an RGB set of signals from a white surface captured by a digital CCD camera, and it increases the number of sensors by using colored filters in front of the camera lens.…”
Section: Discussionmentioning
confidence: 99%
“…The present work has shown, however, that a combination of the direct-mapping method and a conventional RGB digital camera with a limited number of colored filters can provide acceptably accurate estimates, complementing related work on recovering illuminant spectra in natural scenes. 3,34,37,38 Of the different combinations of colored filters, best performance was obtained with three filters. In terms of the three measures, the recovered signal had a goodnessof-fit coefficient better than 99.0%, a root-mean-square error less than 5.0%, and a CIELAB color difference less than 0.27.…”
Section: Discussionmentioning
confidence: 99%
“…The training set was based on grouping the similar spectral radiances, according to their distances measured by the colorimetric and spectral combined metric, defined by M. A. López-Álvarez et al (2005). The third method showed that it is possible to recover zenithal sky radiance spectra, with a reduced number of broadband spectral filters used in the CCD camera.…”
Section: Cloudiness Indexesmentioning
confidence: 99%